Handbook of holistic neuropsychological rehabilitation : outpatient rehabilitation of traumatic brain injury - Ben-Yishay, Yehuda, ....-; Diller, Leonard, ....- (New York, N.Y. : Oxford University Press, 2011)
This clinical guide is the culmination of over three decades of experience in neuropsychological rehabilitation of individuals with traumatic brain injuries. Developed by the experts at the world-renowned Brain Injury Day Treatment Program at New York University Medical Center's Rusk Institute, this text emphasizes the interdependence of cognitive, emotional, and behavioral functions in the human brain. The book articulates the holistic rationale of rehabilitation in a therapeutic community setting, pioneered by Kurt Goldstein. The text is accompanied by five DVDs of edited video clips that illustrate the key organizational, programmatic, and therapeutic clinical procedures that have proven so effective in optimizing the functional competence of brain-injured persons.
Evolution of psychological interventions in rehabilitation -- Essentials of holistic neuropsychological rehabilitation -- Elements of a treatment cycle -- Assembling and training the professional staff -- Identifying and assessing potential program trainees -- Starting a treatment cycle -- Exploiting the "halo" effects from professional visits -- Fostering awareness and self-understanding -- Facilitating compensation in the cognitive domains of functioning -- Contributions of significant others -- Managing interferences with the treatment process -- Questions we are frequently asked.
Includes bibliographical references and index.
Keywords: Brain Injuries -- Psychology; Brain Injuries -- Rehabilitation; Clinical neuropsychology -- Handbooks, manuals, etc; Cognition Disorders -- Etiology; Hersenbeschadigingen; Holisme; Holistic medicine -- Handbooks, manuals, etc; Klinische psychologie; Neuropsychologie; Treatment Outcome; Young Adult